A multilayer piezoelectric electret film element

By adjusting the pore gap and dielectric strength of the polymer porous sheet and combining with the multi-layer structural design, the production efficiency and piezoelectric activity of the polymer porous piezoelectric electret sheet are solved, and piezoelectric with high sensitivity and mechanical strength is achieved Sensors suitable for wearable devices and high temperature environments.

CN118843379BActive Publication Date: 2024-12-13HUBEI XIANGYUAN HIGH-TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411311128.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-13
Estimated Expiration
2044-09-20

Smart Images

  • Figure CN118843379B_ABST
    Figure CN118843379B_ABST
Patent Text Reader

Abstract

The invention provides a multilayer piezoelectric electret film element. By adjusting the pore gap and dielectric strength of a polymer porous sheet in the multilayer piezoelectric electret film element, it is ensured that the gas can be ionized without damaging the polymer porous sheet. After being subjected to electric polarization and surface metallization treatment, the multilayer piezoelectric electret film element has a higher piezoelectric constant and can generate significant charge when subjected to mechanical pressure, thereby showing high sensitivity in applications such as piezoelectric sensors, thereby solving the problems of low piezoelectric activity of the polymer piezoelectric electret film element in the prior art, and rapid loss of piezoelectric activity after polarization. The production process is simple, and continuous production of the polymer piezoelectric electret film element can be guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a thin film element, in particular to a multilayer piezoelectric electret thin film element. Background Art

[0002] With the continuous advancement of science and technology, the demand for high-performance sensors is growing, especially in the field of sound detection and recognition. Polymer porous piezoelectric electret sheets have become a hot topic of research due to their high sensitivity and low acoustic impedance. This material can convert sound energy into electrical signals and is widely used in various small devices such as smartphones and tablets. In addition, the thinness and simple structure of polymer porous piezoelectric electret sheets make it possible to develop new wearable devices. For example, by combining with flexible electronic technology, wearable acoustic and electrical sensors that can monitor human sound signals or changes in environmental sounds can be created, which has great application potential in fields such as medical health monitoring and environmental sound analysis.

[0003] However, there are some challenges in the preparation of polymer piezoelectric electret sheets in the existing technology. The traditional production method is difficult to achieve continuous production, resulting in low production efficiency and unable to meet the needs of large-scale applications. In addition, the prepared piezoelectric sheets often have low piezoelectric activity and lose piezoelectric activity quickly after polarization, which limits its application and development in the field of high-performance sensors.

[0004] In the prior art CN117395581A, a porous polymer piezoelectric electret sheet is disclosed, including but not limited to a polypropylene (PP) sheet. The interior may contain honeycomb convex lens-like holes. Furthermore, the thickness may be between 30 microns and 80 microns. The electroacoustic device made by utilizing the inverse piezoelectric effect of the piezoelectric electret material has advantages in reducing the volume, reducing the number of parts, and improving reliability, and can achieve a higher piezoelectric coefficient and sensitivity. However, in actual production and application, it still faces the above-mentioned problems of low piezoelectric activity and rapid loss of piezoelectric activity after polarization.

[0005] Similarly, the prior art CN116419654A shows the application of piezoelectric electret sheets made of PP material in electroacoustic conversion, but does not completely solve the problems of continuous production and piezoelectric activity stability in the prior art.

[0006] In summary, although the existing technology has made some progress in the application of polymer porous piezoelectric electret film elements, there are still many problems and challenges in material preparation, production efficiency, piezoelectric activity and its stability. These problems limit the further development and wide application of polymer porous piezoelectric electret sheets in the field of acoustic and electrical sensors. Therefore, it is necessary to conduct in-depth analysis and improvement of the existing technology to overcome these challenges and promote technological progress and industrial development in this field. Summary of the invention

[0007] In view of the defects of the prior art, the purpose of the present invention is to provide a multilayer piezoelectric electret film element, aiming to solve the problems of low piezoelectric activity and rapid loss of piezoelectric activity after polarization in the prior art polymer piezoelectric electret film elements, and the production process is simple to ensure the continuous production of polymer piezoelectric electret film elements.

[0008] The present inventors conducted intensive research and found that by adjusting the pore gap and dielectric strength of a polymer porous sheet used for a piezoelectric electret, it is ensured that the gas can be ionized without damaging the polymer porous sheet, thereby completing the present invention.

[0009] That is, the gist of the present invention lies in the following [1]-[3]:

[0010] [1] A multilayer piezoelectric electret film element, comprising a first conductive layer 2, a flexible porous film layer 3 and a second conductive layer 4 in sequence, wherein the flexible porous film layer 3 comprises a polymer porous sheet, wherein the thickness H of the polymer porous sheet is 50 μm-2000 μm, and the density is 100-900 kg / m 3 ;

[0011] D zd The pores in the range of 5 μm to 50 μm account for more than 80% of the total pores in the polymer porous sheet. zd It is defined as the maximum bubble diameter of a single bubble in the thickness direction;

[0012] H p / H is 5%-60%, H p It is defined as the average value of the cumulative thickness of the polymer matrix after excluding the pores in the thickness direction, and H is defined as the thickness of the polymer porous sheet;

[0013] And the dielectric strength of the polymer porous sheet in the thickness direction is 10-60 MV / m.

[0014] [2] A polymer porous sheet, wherein the thickness H of the polymer porous sheet is 50 μm-2000 μm and the density is 100-900 kg / m 3 , D zd The pores in the range of 5 μm to 50 μm account for more than 80% of the total pores in the polymer porous sheet. zd It is defined as the maximum bubble diameter of a single bubble in the thickness direction;

[0015] H p / H is 5%-60%, H p It is defined as the average value of the cumulative thickness of the polymer matrix after excluding the pores in the thickness direction, and H is defined as the thickness of the polymer porous sheet;

[0016] And the dielectric strength of the polymer porous sheet in the thickness direction is 10-60 MV / m.

[0017] [3] A method for preparing a polymer porous sheet, wherein the polymer porous sheet is prepared by foaming a matrix resin, wherein the matrix resin refers to a blended resin of at least two or more blended polyolefin resins that have been melt-blended but not cross-linked and foamed, wherein the matrix resin has a dielectric constant of 2.2-2.4 and a melting peak temperature of 135-150°C; optionally, the matrix resin has a standard cross-linking degree of 40-80% at a radiation dose of 25 Mrad,

[0018] The matrix resin is sequentially subjected to extrusion molding, electron beam radiation cross-linking, normal pressure high temperature foaming, biaxial stretching, and calendering to obtain a polymer porous sheet for a piezoelectric electret.

[0019] Beneficial effects of the present invention:

[0020] The multilayer piezoelectric electret film element of the present invention comprises a polymer porous sheet, which has a high piezoelectric constant after being subjected to electrodeposition and surface metallization treatment, and can generate significant charge when subjected to mechanical pressure, thereby making the multilayer piezoelectric electret film element of the present invention exhibit high sensitivity in applications such as piezoelectric sensors.

[0021] At the same time, the multilayer piezoelectric electret film element of the present invention has good mechanical strength while maintaining softness and recoverability. Its core component, the polymer porous sheet, can maintain good shape stability when compressed or stretched, and has a light texture. It can be better combined with flexible electronic technology to develop wearable acoustic and electrical sensors.

[0022] Furthermore, the core component of the multilayer piezoelectric electret film element in the present invention, the polymer porous sheet, can be used in a high temperature environment of 60° C. while maintaining good shape stability, and its dimensional change rate is controlled between -5% and 5%.

[0023] Moreover, the production process of the present invention is simple and can realize continuous production of materials. Compared with traditional piezoelectric ceramic sensors and piezoelectric sensors based on PVDF, the multilayer piezoelectric electret film element of the present invention has the advantages of low price, light weight, simple structure, etc., which makes it have significant cost-effectiveness advantage in market competition. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a schematic diagram of the structure of a multilayer piezoelectric electret film element;

[0025] Figure 2 Schematic diagram of the calculation of the theoretical cross-section formula of a polymer porous sheet;

[0026] Figure 3 This is the SEM image of the cross section of the polymer porous sheet in Example 1.

[0027] in

[0028] 1-base support layer, 2-first conductive layer, 3-flexible porous film layer, 4-second conductive layer, 5-outer covering layer. DETAILED DESCRIPTION

[0029] The present invention is described in detail below by way of examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art in this field can make some non-essential improvements and adjustments to the present invention based on the above content of the present invention.

[0030] [Multilayer piezoelectric electret film element]

[0031] The multilayer piezoelectric electret thin film element of the present invention is as follows Figure 1 As shown, it includes a base support layer 1, a first conductive layer 2, a flexible porous film layer 3, a second conductive layer 4 and an outer covering layer 5 in sequence, wherein the base support layer 1 and the outer covering layer 5 are not necessary depending on the application scenario, and the multilayer piezoelectric electret film element may only include the first conductive layer 2, the flexible porous film layer 3 and the second conductive layer 4 in sequence in some application scenarios.

[0032] The flexible porous film layer 3 is the core component of the present invention, which has a piezoelectric effect. The piezoelectric effect can directly convert mechanical energy into electrical signals. In the multilayer piezoelectric electret film element, it is laid on the base support layer 1 in the form of a film. In order to achieve all-round perception of three-dimensional space, the piezoelectric film can be designed in an array form, or even distributed in a complex pattern such as a grid or spiral, so as to improve the tactile resolution and positioning accuracy. The specific material design is described in detail in the following content.

[0033] The base support layer 1 is made of soft and elastic polymer materials, such as silicone rubber, polyurethane, etc., to provide physical support and ductility for the skin, ensuring that it can adapt to various complex surface deformations.

[0034] The first conductive layer 2 and the second conductive layer 4 are used to collect and transmit the electrical signals generated by the piezoelectric film. The layer can be a metal nanowire network, carbon nanotubes, graphene or conductive polymer, etc. They have good conductivity and flexibility, can be closely combined with the piezoelectric film, and ensure the effective transmission of electrical signals.

[0035] The outer coating 5 is used to protect the internal structure from environmental influences, and is usually made of wear-resistant, moisture-proof and corrosion-resistant materials, such as Teflon coating, flexible glass, etc., to ensure the long-term stability and reliability of the multilayer piezoelectric electret thin film element.

[0036] Multilayer piezoelectric electret film elements are very suitable for applications that require high sensitivity and adaptability to complex surfaces due to their soft and flexible texture. For example, they can be integrated into smart watches and health bracelets to monitor physiological parameters such as heart rate, blood pressure, and respiratory rate to provide users with real-time health data; or applied to robot skin structures to give robots more delicate tactile perception and more natural interaction capabilities.

[0037] [Polymer porous sheet]

[0038] The polymer porous sheet of the present invention is mainly used in piezoelectric electret film elements, as the material composition of the flexible porous film layer 3, has a porous structure, the polymer matrix is ​​separated by pores, and a structure in which the matrix and the pores are staggered in the thickness direction is formed. During the polarization process, the gas molecules in the pores are ionized to generate positive and negative charges. These charges are deposited on the surface of the polymer matrix under the action of the electric field to form a stable charge distribution. Due to the isolation effect of the pores, these charges can still be retained in the material after the external electric field is removed, thereby giving the material lasting piezoelectric properties.

[0039] In addition to being used in piezoelectric electret film elements, the polymer porous sheet of the present invention can also be used in protective buffer plates for vehicle-mounted components and displays due to its heat resistance, buffering properties, and ability to protect antenna components from interference from clutter.

[0040] The orderly arrangement of polymer layers and pores in the thickness direction of the polymer porous sheet enables the material to produce a significant charge response in a local area when subjected to mechanical stress. This localized charge response manifests itself as a piezoelectric effect of the entire material on a macroscopic level, that is, the material can generate an electrical signal when subjected to pressure or stretching.

[0041] <Thickness>

[0042] The thickness of the polymer porous sheet of the present invention is preferably 50 μm or more, preferably 80 μm or more, more preferably 100 μm or more, further preferably 150 μm or more, and further preferably 200 μm or more, from the perspective of material breakdown due to too thin a thickness and from the perspective of improving material strength and mechanical durability.

[0043] From the perspective of adhesion and flexibility, as well as the perspective of polarization uniformity, it is 2000 μm or less, preferably 1000 μm or less, more preferably 900 μm or less, further preferably 800 μm or less, and further preferably 700 μm or less.

[0044] If a moderate thickness range is selected in this way, for the polymer porous sheet, it can provide sufficient dielectric strength and maintain a high piezoelectric constant, while ensuring ideal softness, adhesion and mechanical strength durability, while taking into account the contradictory technical problems of preventing the material from being broken down during polarization and uneven polarization.

[0045] <Cells>

[0046] In addition to the polymer matrix, the rest of the polymer porous sheet is filled with pores. There is gas in the pores, which can be polarized and generate charges under the action of an electric field. Commonly used gases include: air, nitrogen, oxygen, argon, carbon dioxide, fluorine, chlorine, water vapor, etc. Based on the comprehensive consideration of cost, polarization effect and maintaining chemical inertness during polarization, air or nitrogen is preferred.

[0047] Due to the presence of pores, the density of the polymer porous sheet of the present invention is lower than that of the polymer matrix. From the perspective of improving mechanical durability and dielectric strength, the density is 100 kg / m 3 Above, preferably 150kg / m 3 More preferably 200 kg / m 3 More preferably, 250 kg / m 3 From the perspective of improving the softness and piezoelectric activity of the polymer porous sheet, the density is 900 kg / m 3 Below, preferably 850 kg / m 3 Below, more preferably 800 kg / m 3 Below, more preferably 600kg / m 3 The density of the polymer porous sheet is measured according to GB_T 40872-2021. From the perspective of piezoelectric conversion, if the density of the polymer porous sheet is less than 100 kg / m 3 , the dielectric strength of the material decreases and it may be broken down during the polarization process, which will damage the piezoelectric properties of the material and may cause permanent loss of performance; the density of the polymer porous sheet is greater than 900kg / m 3 , there is insufficient gas available for ionization in the pores, the polarization activity is reduced, and the polymer material may be too dense, which limits the mobility of the polymer chains, thereby reducing the charge generated under mechanical stress and resulting in reduced piezoelectric activity.

[0048] The structural position relationship of the pores in the polymer porous sheet has a great influence on the piezoelectric performance. The piezoelectric electret sheet formed by the polymer porous sheet of the present invention is usually bonded to the flexible lower electrode and the flexible upper electrode. The piezoelectric effect is usually generated in the thickness direction of the polymer porous sheet. Therefore, the present invention focuses on the distribution of pores in the thickness direction of the polymer porous sheet.

[0049] Definition D zd is the maximum bubble diameter of a single bubble in the thickness direction. Specifically, D zd It is done by selecting two points on the surface of a single cell, the line between the two points is parallel to the thickness direction of the material, and the distance between the two points is the maximum value among all possible point pairs. In other words, D zd It is the longest straight-line distance between the two surfaces of the pore in the material thickness direction, measured along the thickness direction. D can be effectively measured by microscope measurement, 3D scanning and other measurement technologies. zd The value of D zd The regulation of the size is of great significance for polymer porous sheets to maintain high dielectric strength and piezoelectric constant in the thickness direction. zd The average value is 10-80 μm, preferably 15-75 μm, and more preferably 20-60 μm.

[0050] The researchers found that D zd When the pores of 5 μm to 50 μm account for more than 80% of the total pores of the polymer porous sheet, the dielectric strength and piezoelectric constant can be kept high at the same time, preferably more than 85%, more preferably more than 90%, and more preferably more than 95%. zd When the pores of 5μm-50μm account for less than 80% of the total pores of the polymer porous sheet, the following unfavorable conditions may exist in terms of pore distribution:

[0051] ①The average pore size is too large, and most of the pores have a D zd Above 50 μm, the number of pores in the range of 5 μm-50 μm does not exceed 80% of the total number of pores in the polymer porous sheet. At this time, the polymer matrix is ​​relatively small in the thickness direction, and the pore part is large. The dielectric strength is reduced, resulting in easier electrical breakdown under the same electric field strength.

[0052] ② The average pore size is small, and most of the pores have a D zdBelow 5μm, the pores between 5μm and 50μm do not account for more than 80% of the total number of pores in the polymer porous sheet. This indicates that the pores in the polymer porous sheet are small, the continuity of the polymer matrix is ​​increased, and the deformation of the polymer chain and the reorientation of the polar groups are essential for the generation of charge. If the pores are too dense, the movement of the polymer chain may be restricted, thereby reducing the amount of charge generated under mechanical stress, resulting in a decrease in the piezoelectric constant of the material.

[0053] ③ The pore size shows a bimodal distribution, but the proportion of pores falling within the range of 5μm-50μm is not high. Due to the uneven pore size, it is easy to cause uneven polarization of the material, which in turn affects the stability and reliability of the overall dielectric strength and piezoelectric constant of the material.

[0054] Moreover, the polymer porous sheet forms an alternating pattern of polymer matrix and pores in the thickness direction, such as Figure 2 As shown. Define H p is the average value of the cumulative thickness of the polymer matrix after excluding the pores in the thickness direction. Figure 2 It can be seen from the figure that in the thickness direction, the polymer matrix is ​​divided into multiple layers by the pores. When describing the cumulative thickness of the polymer matrix of the polymer porous sheet in the thickness direction, H is defined pn is the cumulative thickness of the polymer matrix from a certain upper surface to the lower surface of the polymer porous sheet parallel to the thickness direction, and H p is the total number of H pn The average value can be expressed by the following formula:

[0055] ;

[0056] Where N is the number of randomly selected points on the entire polymer porous sheet. Usually, on a 5 cm × 5 cm polymer porous sheet sample, N points are not less than 50. The larger N is, the closer it is to the true H of the entire polymer porous sheet. p average value.

[0057] In the present invention, H p / H is 5%-60%, H is the thickness of the polymer porous sheet, which is explained in the <Thickness> section. Here, it is further clarified that it is the sum of the thickness of the polymer matrix and the pores in the thickness direction. Preferably H p / H is 10-50%, more preferably 15-45%, and more preferably 20-40%. Within this range, the distribution of the polymer matrix and the pores in the thickness direction of the polymer porous sheet is reasonable, which can take into account mechanical strength, dielectric strength, and polarization efficiency, thereby improving the stability and reliability of the application of the polymer porous sheet.

[0058] In the present invention, the porosity of the polymer porous sheet is less than 20%, preferably less than 15%, more preferably less than 10%, and more preferably less than 7%. If the porosity of the polymer porous sheet is too high, greater than 20%, more open holes are formed, which will cause electric field leakage, reduce the electric field strength inside the material, and then reduce the dielectric strength, and because the charge may leak out through the open holes, this will reduce the polarization efficiency and piezoelectric activity of the material. At the same time, when the closed porosity in the polymer porous sheet is improved, when impacted, the deformation of the pores can be suppressed, thereby, the deformation of the polymer porous sheet relative to the impact can also be suppressed, therefore, it is easy to further improve the impact absorbency.

[0059] <Polymer Matrix Component>

[0060] For the polymer porous sheet of the present invention, the polymer matrix resin at least includes a polypropylene resin. Considering the dielectric strength, piezoelectric constant and foaming performance, the polyolefin resin is preferably a propylene homopolymer or a mixture of a polypropylene resin and other resins.

[0061] As polypropylene resins, for example, propylene homopolymers, propylene-ethylene copolymers, propylene-ethylene-α-olefin copolymers, and propylene-α-olefin copolymers can be cited. One of them can be used alone, or two or more can be used in combination. And as α-olefins constituting propylene-α-olefin copolymers, specifically, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, etc. can be cited, among which α-olefins with 6 to 12 carbon atoms are preferred. Among them, for propylene copolymers, the content of propylene in the copolymer is 50wt% or more, and can further be 60wt% or more, 70wt% or more, 80wt% or more, 90wt% or more, 95wt% or more, and 99wt% or more.

[0062] As a mixture of a polypropylene resin and other resins, other resins include polyethylene resins, vinyl chloride resins (polyvinyl chloride, PVC), polystyrene (PS), polyurethane resins (PU), polycarbonate (PC), polyacetal (POM), polyphenylene ether (PPE), methacrylic resin (PMMA), acrylonitrile styrene resin (SAN), non-crystalline polyethylene terephthalate (PETG), polyimide resin (PI), polyolefin plastomer (POP), polyamide-imide resin, polyarylate, polysulfone (PSU), polyethylene naphthalate (PEN), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), acrylonitrile-butadiene-styrene resin (ABS), fluororesin (PTFE, PCTFE, etc.), preferably blended with polyethylene resin and / or polyolefin plastomer. Considering the control of dielectric strength and piezoelectric properties and the compatibility of polymers, when polypropylene is blended with other polymers, the content of polypropylene is 40-80wt% of the total polymer content, and can further be 45wt%, 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, 75wt%.

[0063] In one embodiment, the polymer matrix resin of the polymer porous sheet includes at least two or more blended polyolefin resins, whereby the matrix resin refers to a blended resin that has not been crosslinked and foamed after at least two or more blended polyolefin resins are melt-blended, and the dielectric constant of the matrix resin is 2.2-2.4 and the melting peak temperature is 135-150° C. Further, the standard crosslinking degree is 40-80% at a radiation dose of 25 Mrad.

[0064] When the matrix resin is selected from the polymers of the above types and contents of the present invention, the dielectric constant is usually in the range of 2.2-2.4. The blended resin in this dielectric constant range helps to maintain stable charge accumulation during the polarization process, thereby improving the piezoelectric properties of the overall polymer porous sheet. The resin component with a high melting temperature characteristic helps to maintain the mechanical strength and chemical stability of the material under high temperature conditions; and the cross-linkability of the blended resin gives the final polymer porous sheet cross-linkability, and the cross-linkability of the final product is described in detail in the following subsections. The selection and control of the peak melting temperature of the matrix resin and the standard cross-linking degree at a radiation dose of 25 Mrad are important control factors that ultimately reflect the pore size and distribution of the foam cells after foaming and cross-linking. And those skilled in the art can make the blended resin have the above-mentioned performance characteristics by selecting a polyolefin resin component of a reasonable type and structure.

[0065] <Crosslinking>

[0066] From the perspective of improving the controllability of the pores of the polymer porous sheet and the softness of the polymer porous sheet, the polymer porous sheet of the present invention is a cross-linked foamed sheet with a cross-linking degree of 10-70%. On this basis, the cross-linking degree is preferably 15% or more, more preferably 20% or more, and the cross-linking degree is preferably 65% ​​or less, more preferably 60% or less. When the cross-linking degree is less than 10%, the polymer porous sheet lacks sufficient mechanical strength and structural stability, causing the material to be easily deformed or broken when subjected to external force, affecting the actual durability; when the cross-linking degree is higher than 70%, the material becomes too hard and fragile, which is not conducive to its application in flexible electronic devices. At the same time, because the excessively high cross-linking degree will limit the movement of the polymer chain, it may also cause the dielectric strength and piezoelectric properties of the material to decrease.

[0067] In one embodiment, based on the control of the type of polymer matrix and the control of the degree of crosslinking, the polymer porous sheet contains a soluble part in xylene and an insoluble part in xylene; wherein the area of ​​the soluble part with a DSC melting temperature above 130°C accounts for 10%-40% of the total area of ​​the DSC melting temperature. The area proportion of the soluble part with a DSC melting temperature above 130°C reflects the content of the soluble polypropylene part. When it is within this range, it can promote the polymer regularity and crystallinity of the overall polymer porous sheet, making the stability of the space charge better. The insoluble part is a cross-linked amorphous region, which provides the mechanical strength and chemical stability of the material, but the excessive crosslinking limits the mobility of the molecular chain, which is not conducive to the free distribution and storage of the charge inside it. The area of ​​the soluble part with a DSC melting temperature below 130°C is polyethylene, which can also provide better charge storage capacity, processing performance and softness, but its charge storage stability is not good. Therefore, in order to improve the charge storage capacity and storage stability of the material, as well as the processing performance and material flexibility, it is necessary to control not only the cross-linking degree of the material, but also the PP content of the uncross-linked part, that is, the area proportion of the soluble part with a DSC melting temperature above 130°C. Preferably, the area proportion of the soluble part with a DSC melting temperature above 130°C is 15%-35%, and more preferably 20%-30%.

[0068] <Dimensional stability>

[0069] The polymer porous sheet of the present invention exhibits excellent dimensional stability under high temperature conditions. Under the test condition of 60°C, the dimensional change rate of the polymer porous sheet is maintained in the range of -5% to 5%, and this range is preferably -3% to 3% to ensure the reliability and performance consistency of the material under various environmental conditions. If the dimensional change rate exceeds this range, for example, greater than 5%, it may cause deformation or performance degradation of the material in high temperature applications, thereby affecting its applicability and durability in more precise flexible electrets.

[0070] <Compressive stress>

[0071] The polymer porous sheet of the present invention exhibits a stress range of 0.5KPa to 150KPa under 10% compression, and this range is preferably 1KPa to 100KPa to ensure the mechanical stability and reliability of the material when subjected to slight to moderate pressure. If the compressive stress is lower than the lower limit of the numerical range, for example, less than 0.5KPa, the material may not be able to withstand the expected load in practical applications, affecting its performance as a structural material; and if the compressive stress is higher than 150KPa, the material may be too fragile, increasing the risk of fatigue failure in long-term use.

[0072] [Preparation process]

[0073] The present invention discloses a method for preparing a polymer porous sheet for a piezoelectric electret. The polymer matrix of the polymer porous sheet comprises at least two or more blended polyolefin resins, wherein at least one of the resins has a dielectric strength greater than 18 MV / m at room temperature, wherein at least one of the resins has a melting peak temperature above 120° C., wherein at least one of the resins can be cross-linked under electron beam radiation, and when the radiation dose is 25 Mrad, the gel content is 10-80%.

[0074] The polyolefin resin is sequentially subjected to extrusion molding, cross-linking process, normal pressure and high temperature foaming, biaxial stretching, and calendering to obtain a polymer porous sheet for a piezoelectric electret.

[0075] Each process step is as follows:

[0076] <Extrusion molding>

[0077] In the extrusion step, the polyolefin resin mixture passes through the extruder head to form a continuous sheet with a specific thickness. During this process, the extrusion temperature is maintained between 130°C and 140°C to ensure sufficient plasticization of the resin and uniformity of the sheet. The extrusion speed is controlled at 2-20m / min to ensure the continuity and consistency of the sheet.

[0078] <Electron beam radiation cross-linking process>

[0079] After the mixed extrusion of the polyolefin matrix resin is completed, the present invention performs a gelation reaction process, i.e., a crosslinking reaction. The crosslinking can be performed by the known technology disclosed in the prior art, such as radiation crosslinking or chemical crosslinking, preferably radiation crosslinking.

[0080] Radiation crosslinking is crosslinking by irradiating the resin sheet with ionizing radiation such as electron beams, α-rays, β-rays, and γ-rays. The irradiation amount of the above-mentioned ionizing radiation is adjusted in such a way that the crosslinking degree of the obtained foam sheet becomes the above-mentioned desired range, for example, 10Mrad-30Mrad, preferably 12Mrad-28Mrad, and more preferably 15Mrad-25Mrad. The energy of radiation crosslinking will affect the rate of crosslinking, and is usually selected to be 1.0Mev-3.0Mev, preferably 1.2Mev-2.8Mev, and more preferably 1.5Mev-2.5Mev.

[0081] A cross-linking aid may be added to reduce the amount of ionizing radiation in the radiation cross-linking step and prevent the cleavage and degradation of resin molecules caused by irradiation with ionizing radiation.

[0082] As a crosslinking aid, specifically, there can be cited trimethylolpropane trimethacrylate, trimethylolpropane triacrylate, trimellitic acid triallyl ester, 1,2,4-benzenetricarboxylic acid triallyl ester, triallyl isocyanurate and other compounds having three functional groups in one molecule, or 1,6-hexanediol dimethacrylate, 1,9-nonanediol dimethacrylate, 1,10-decanediol dimethacrylate, divinylbenzene and other compounds having two functional groups in one molecule, diallyl phthalate, diallyl terephthalate, diallyl isophthalate, ethylvinylbenzene, neopentyl glycol dimethacrylate, lauryl methacrylate, stearyl methacrylate and the like. These crosslinking aids are used alone or in combination of two or more. The content of the crosslinking aid is 0.1%-1wt% based on the total weight of the polymer matrix resin.

[0083] <Normal pressure and high temperature foaming>

[0084] The crosslinked sheet-shaped polyolefin resin composition is heated to foam a thermally decomposable foaming agent, and as the thermally decomposable foaming agent, for example, a foaming agent having a decomposition temperature higher than the melting temperature of the resin is used, for example, an organic or inorganic chemical foaming agent having a decomposition temperature of 160 to 270°C is used.

[0085] Examples of the organic foaming agent include azodicarbonamide, azodicarboxylic acid metal salts (barium azodicarboxylate and the like), azo compounds such as azobisisobutyronitrile, nitroso compounds such as N,N'-dinitrosopentamethylenetetramine, hydrazonodicarbonamide, 4,4'-oxybis(benzenesulfonylhydrazide), hydrazine derivatives such as toluenesulfonylhydrazide, and semicarbazide compounds such as toluenesulfonylsemicarbazide.

[0086] Examples of the inorganic foaming agent include ammonium carbonate, sodium carbonate, ammonium hydrogen carbonate, sodium hydrogen carbonate, ammonium nitrite, sodium borohydride, and anhydrous monosodium citrate.

[0087] Among these, from the viewpoint of obtaining fine bubbles, economic efficiency and safety, azo compounds and nitroso compounds are preferred, azodicarbonamide, azobisisobutyronitrile and N,N'-dinitrosopentamethylenetetramine are more preferred, and azodicarbonamide is further preferred. Azodicarbonamide is preferred. The thermal decomposition type foaming agent may be used alone or in combination of two or more.

[0088] The amount of the thermally decomposable foaming agent added is preferably 1 to 10 parts by mass, more preferably 1.5 to 5 parts by mass, and even more preferably 1.5 to 3 parts by mass, based on 100 parts by mass of the polyolefin-based resin.

[0089] The temperature for heating and foaming varies depending on the decomposition temperature of the thermally decomposable foaming agent, but is generally 140 to 300°C, preferably 160 to 260°C when an azo compound foaming agent is used.

[0090] In addition, a foaming aid can be added to help adjust the decomposition temperature and decomposition rate of the foaming agent. The foaming aids compatible with the azo foaming agent include urea, phosphate, organic acid, and metal salt foaming aids, preferably metal salt foaming aids, and more preferably metal zinc salt foaming aids such as zinc oxide, stearic acid and zinc stearate.

[0091] The polymer porous sheet of the present invention may also be added with other functional additives during the foaming and molding process according to the application scenario. Other functional additives include but are not limited to: processing aids, flame retardants, antistatic agents, etc.

[0092] <Bidirectional stretch>

[0093] Stretching can be performed after the polyolefin resin composition is foamed to obtain a polymer porous sheet, or can be performed while the polyolefin resin composition is foamed. It should be noted that when the polymer porous sheet is stretched after the polyolefin resin composition is foamed to obtain a polymer porous sheet, it is preferred that the polymer porous sheet is not cooled and the polymer porous sheet is stretched continuously while maintaining the molten state during foaming, but it is also possible to heat the polymer porous sheet again after cooling the polymer porous sheet to make it molten or softened and then stretch the polymer porous sheet.

[0094] The stretching ratio in the MD direction of the polymer porous sheet is preferably 1.1 to 3.2 times, more preferably 1.3 to 3.0 times. If the stretching ratio in the MD direction of the polymer porous sheet is above the above lower limit, the thermal insulation, flexibility and tensile strength of the polymer porous sheet are easily improved. On the other hand, if the stretching ratio in the MD direction of the polymer porous sheet is below the upper limit, the polymer porous sheet can be prevented from breaking during stretching or the foaming gas can be prevented from escaping from the polymer porous sheet in foaming, thereby reducing the foaming ratio. The flexibility and tensile strength of the polymer porous sheet are improved, and the quality is also easily uniform. In addition, the polymer porous sheet is preferably stretched along the TD direction at the stretching ratio in the above range.

[0095] <Calendering and shaping>

[0096] In the calendering step, the polymer porous sheet is compacted and flattened by a calender. The calendering pressure is set to 8-15MPa and the calendering speed is set to 5-10m / min to ensure the smoothness and uniformity of the sheet. During the calendering process, the temperature of the calendering roller surface is maintained between 80℃ and 120℃ to adapt to the physical properties of the sheet. Finally, a polymer porous sheet with a thickness H of 50μm-2000μm is obtained.

[0097] [Piezoelectric electret film]

[0098] The present invention further discloses a piezoelectric electret sheet, comprising the polymer porous sheet of the present invention. The piezoelectric electret sheet is formed by subjecting the polymer porous sheet to electrodeposition and surface metallization treatment.

[0099] <Polarization process>

[0100] The polymer porous sheet of the present invention is charged by a normal pressure negative corona discharge method, the negative voltage Vp applied to the upper electrode is -16 to -8 KV, the distance d between the corona needle and the surface of the polymer porous sheet is 2 to 4 cm, and the charging time t p The corona voltage should be regulated to avoid spark discharge between the needle and the membrane. After the sample is polarized by corona charging, it is placed at room temperature and pressure for a period of time until the charge distribution is stable, and then the double-sided electrode is evaporated.

[0101] The sample can also be charged by the contact method (PNC 20000-3ump, Heinzinger, Germany). The sample charged by the contact method has electrodes evaporated on both sides before charging. The contact method charging voltage is 4-8KV, the charging time is 2-20s, and the charging temperature is 20-120℃.

[0102] <Surface Metallization>

[0103] The polarized polymer porous sheet is then subjected to surface metallization, a step that is critical for forming an effective electrode and improving electrical conductivity. Surface metallization can be achieved through physical vapor deposition (PVD), chemical vapor deposition (CVD) or electroplating. In the PVD process, metal or alloy materials are evaporated and deposited on both surfaces of the polymer porous sheet in a vacuum environment to form a uniform, dense metal film. In the CVD process, the metal precursor is decomposed or reduced under controlled temperature and pressure conditions to generate a metal film that is deposited on the polymer porous sheet.

[0104] [application]

[0105] The piezoelectric electret film made of the polymer porous sheet of the present invention can be used in the fields of flexible piezoelectric sensors, audio transducers, micro energy harvesters, etc. In addition to being used in piezoelectric electret film elements, the polymer porous sheet can also be used in protective buffer plates of vehicle-mounted components and displays due to its heat resistance and buffering properties and its ability to protect antenna components from interference by clutter.

[0106] [Test conditions]

[0107] The performance index determination method involved in the present invention is as follows:

[0108] <density>

[0109] The density of the polymer porous sheet is measured according to the provisions of GB_T 40872-2021.

[0110] <Cell diameter D in thickness direction zd and the average value of the cumulative thickness of the polymer matrix H p >

[0111] Samples were taken at random positions of the polymer porous sheet, and cross-sectional cell images of the polymer porous sheet were taken using SEM, and the thickness and pore size of the polymer porous sheet were measured using SEM cell measurement software, and the number of cells with different pore sizes was counted to calculate the average pore size. The pore size is the pore size in the direction perpendicular to the thickness direction.

[0112] <Opening Rate>

[0113] The open porosity of the polymer porous sheet was tested using the test method in GB-T 10799-2008 Determination of open and closed cell volume percentage of rigid foam plastics.

[0114] <Determination of degree of cross-linking>

[0115] a. Take 100 mg of sample from the polymer porous sheet and accurately weigh the weight A (mg) of the sample;

[0116] b. Wrap the specimen with a 200-mesh metal screen, and immerse the specimen wrapped with the metal screen in xylene at 120 °C for 24 hours. Through the filtering action of the metal screen, the insoluble matter can be collected inside the metal screen; after vacuum drying, accurately weigh the weight B (mg) of the insoluble matter;

[0117] c. Calculate the crosslinking degree (mass %):

[0118] Crosslinking degree (mass %) = 100 %×(B / A).

[0119] <Dimensional change rate at 60 °C>

[0120] Conduct according to the provisions of GB / T8811. The test temperature is (60±5) °C, and the time is (20±1) h. The sample size should be (150±5) mm×(150±5) mm, with a flat surface, parallel up and down, and the thickness is the original thickness of the sample.

[0121] <Elongation at break>

[0122] Conduct according to the provisions of GB / T6344. The tensile speed of the testing machine is (500±50) mm / min. For materials with a thickness less than 10 mm, measure according to the original thickness. For materials with a thickness greater than or equal to 10 mm, the sample thickness is set to (10±1) mm.

[0123] <10% Compressive stress>

[0124] Conduct according to the provisions of GB / T18942.1. The sample thickness should be at least 10 mm. For relatively thin materials, the samples should be stacked to at least 10 mm. Apply a prestress of (100±10) Pa to the sample before the test starts. After completing the preload, zero the compression indication of the compression measurement system. The test should compress the sample at a rate of (50±10)% of the initial thickness of the sample per minute. Measure the compressive stress when the sample is compressed by 10% for the first time.

[0125] <Dielectric strength test / Breakdown voltage strength>

[0126] Test the breakdown voltage in the thickness direction of the sample according to GB / T 1695-2005. The test temperature is 23 °C±2. Set square plate-shaped electrodes with a side length of 50±1 mm. Apply a voltage frequency of 50 Hz and a voltage rise rate of 500 V / s. When the sample is broken down under a certain voltage, the voltage value at this time is called the breakdown voltage. The dielectric strength (breakdown voltage strength) of the sample is the ratio of the breakdown voltage to the thickness of the sample.

[0127] <D33 Piezoelectric constant>

[0128] After polarization and surface electrode treatment, measure the piezoelectric d33 coefficient of the charged sample using the static method

[0129] 1. Experimental preparation:

[0130] Prepare the PP piezoelectric film sample and ensure that its surface is clean and undamaged. Use the ZJ-3AN quasi-static d33 measuring instrument or other high-precision piezoelectric coefficient tester. Confirm that the instrument has been calibrated and meets the test requirements, including high-precision equipment with a resolution of at least 0.01pC / N.

[0131] 2. Sample installation:

[0132] Correctly install the PP piezoelectric film sample into the fixture of the tester, ensuring that the force direction of the sample is consistent with the polarization direction of the film, because the d33 coefficient is the piezoelectric response measured along the polarization direction.

[0133] 3. Short circuit and grounding:

[0134] Before applying force, according to experimental requirements, it is necessary to close the switch K1 to short-circuit the sample to eliminate the transient charge generated during pressure application and reduce measurement errors.

[0135] 4. Apply force and measure:

[0136] According to the experimental procedure, a predetermined force F3 is applied slowly and evenly to the film sample while the amount of charge generated is monitored and recorded.

[0137] The application of force should be controlled under quasi-static conditions to avoid dynamic effects caused by rapid changes that interfere with the measurement results.

[0138] 5. Data collection and analysis:

[0139] Based on the measured charge and applied force, the d33 coefficient is calculated using the formula d33=Q / F, where Q is the amount of charge generated and F is the applied force.

[0140] Hereinafter, the present invention will be described by referring to several embodiments, but the present invention is not intended to be limited to these embodiments.

[0141] Example 1

[0142] 20 parts by weight of linear low-density polyethylene (LLDPE, trade name: Hanhua CLBA-8250BK), 20 parts by weight of polyolefin plastomer (POP, trade name: AFFINITY™ PL 1850G), 60 parts by weight of cross-linkable polypropylene (PP, trade name: HC300B), 10 parts by weight of foaming masterbatch containing 95wt% of azobisisobutyronitrile and 5wt% of zinc oxide, 0.5 parts by weight of trimethylolpropane trimethacrylate (cross-linking aid, trade name; LightEster TMP, manufactured by Kyoeisha Chemical Co., Ltd., non-volatile component: 100wt%), 0.5 parts by weight of antioxidant (phenolic antioxidant Irganox 1010), 0.1 parts by weight of ultraviolet light absorber (Tinuvin 326), and 0.5 parts by weight of processing aid (a mixture of paraffin oil and erucamide) are mixed in a high-speed mixer, then kneaded at 135°C, and then extruded into strip sheets; at this time, the melting peak temperature of the matrix resin is 145.1°C, the dielectric constant is 2.31, and the gel content at a radiation dose of 25 Mrad is 61%.

[0143] The extruded resin sheet was irradiated on both sides with electron rays, with an irradiation energy of 1.5 MeV and an irradiation dose of 15.3 Mrad, so that the resin sheet was cross-linked;

[0144] The cross-linked resin sheet was then sent to a heating furnace for foaming at 200°C, and then the temperature was lowered to 120°C for biaxial stretching, with the sheet being stretched 1.5 times in the TD direction and 1.8 times in the MD direction.

[0145] Then, the calendering step was performed, the calendering pressure was 12 MPa, and the calendering speed was set to 8 m / min; after calendering, a 300 μm polymer porous sheet was obtained. The cross section was scanned by SEM to observe its porous distribution, such as Figure 3 shown.

[0146] Example 2

[0147] 30 parts by weight of linear low-density polyethylene (LLDPE, trade name: Hanhua CLBA-8250BK), 30 parts by weight of polyolefin plastomer (POP, trade name: AFFINITY™ PL 1850G), 40 parts by weight of cross-linkable polypropylene (PP, trade name: HC300B), 10 parts by weight of foaming masterbatch containing 95 wt% of azobisisobutyronitrile and 5 wt% of zinc oxide, 0.5 parts by weight of trimethylolpropane trimethacrylate (cross-linking aid, trade name; Light Ester TMP, manufactured by Kyoeisha Chemical Co., Ltd., non-volatile component: 100% by weight), 0.5 parts by weight of antioxidant (phenolic antioxidant Irganox 1010), 0.1 parts by weight of ultraviolet light absorber (Tinuvin 326), 0.5 weight part of processing aid (mixture of paraffin oil and erucamide) was mixed in a high-speed mixer, then kneaded at 135°C, and then extruded into strip sheets; at this time, the dielectric constant of the matrix resin was 2.23, the melting peak temperature was 135.2°C, and the gel content was 79% at a radiation dose of 25 Mrad.

[0148] The extruded resin sheet was irradiated on both sides by electron beams, with an irradiation energy of 1.5 MeV and an irradiation dose of 13.2 Mrad, so that the resin sheet was cross-linked;

[0149] The cross-linked resin sheet was then sent to a heating furnace for foaming at 200°C, and then the temperature was lowered to 120°C for biaxial stretching, with the sheet being stretched 1.5 times in the TD direction and 1.8 times in the MD direction.

[0150] Then, a calendering step is performed, and the calendering pressure and calendering speed are controlled so that a 350 μm polymer porous sheet is obtained after calendering.

[0151] Example 3

[0152] 20 parts by weight of linear low-density polyethylene (LLDPE, trade name: Hanhua CLBA-8250BK), 80 parts by weight of cross-linkable polypropylene (PP, trade name: HC300B), 10 parts by weight of foaming masterbatch containing 95 wt% of azobisisobutyronitrile and 5 wt% of zinc oxide, 0.5 parts by weight of trimethylolpropane trimethacrylate (cross-linking aid, trade name; Light Ester TMP, manufactured by Kyoeisha Chemical Co., Ltd., non-volatile component: 100% by weight), 0.5 parts by weight of antioxidant (phenolic antioxidant Irganox 1010), 0.1 parts by weight of ultraviolet light absorber (Tinuvin 326), and 0.5 parts by weight of processing aid (a mixture of paraffin oil and erucamide) were mixed in a high-speed mixer, then kneaded at 135° C., and then extruded into strip sheets; at this time, the dielectric constant of the matrix resin was 2.23 The melting peak temperature is 149.5°C and the gel content is 32% at a radiation dose of 25 Mrad.

[0153] The extruded resin sheet was irradiated on both sides with electron rays, with an irradiation energy of 1.5 MeV and an irradiation dose of 15.3 Mrad, so that the resin sheet was cross-linked;

[0154] The cross-linked resin sheet was then sent to a heating furnace for foaming at 200°C, and then the temperature was lowered to 120°C for biaxial stretching, with the sheet being stretched 1.5 times in the TD direction and 1.8 times in the MD direction.

[0155] Then, a calendering step is performed, and the calendering pressure and calendering speed are controlled so that a 1500 μm polymer porous sheet is obtained after calendering.

[0156] Example 4

[0157] 20 parts by weight of linear low-density polyethylene (LLDPE, trade name: Hanhua CLBA-8250BK), 20 parts by weight of polyolefin plastomer (POP, trade name: AFFINITY™ PL 1850G), 60 parts by weight of cross-linkable polypropylene (PP, trade name: HC300B), 15 parts by weight of foaming masterbatch containing 95 wt% of azobisisobutyronitrile and 5 wt% of zinc oxide, 0.5 parts by weight of trimethylolpropane trimethacrylate (cross-linking aid, trade name; Light Ester TMP, manufactured by Kyoeisha Chemical Co., Ltd., non-volatile component: 100% by weight), 0.5 parts by weight of antioxidant (phenolic antioxidant Irganox 1010), 0.1 parts by weight of ultraviolet light absorber (Tinuvin 326), 0.5 weight part of processing aid (mixture of paraffin oil and erucamide) was mixed in a high-speed mixer, then kneaded at 135°C, and then extruded into strip sheets; at this time, the dielectric constant of the matrix resin was 2.31, the melting peak temperature was 145.1°C, and the gel content was 61% at a radiation dose of 25 Mrad.

[0158] The extruded resin sheet was irradiated on both sides with electron beams, with an irradiation energy of 1.5 MeV and an irradiation dose of 14.7 Mrad, so that the resin sheet was cross-linked;

[0159] The cross-linked resin sheet was then sent to a heating furnace for foaming at 240°C, and then the temperature was lowered to 120°C for biaxial stretching, with the sheet being stretched 1.35 times in the TD direction and 1.35 times in the MD direction.

[0160] Then, a calendering step is performed, and the calendering pressure and calendering speed are controlled so that a 530 μm polymer porous sheet is obtained after calendering.

[0161] Example 5

[0162] 30 parts by weight of linear low-density polyethylene (LLDPE, trade name: Hanhua CLBA-8250BK), 270 parts by weight of cross-linkable polypropylene (PP, trade name: HC300B), 5 parts by weight of foaming masterbatch containing 95 wt% of azobisisobutyronitrile and 5 wt% of zinc oxide, 0.8 parts by weight of trimethylolpropane trimethacrylate (cross-linking aid, trade name; Light Ester TMP, manufactured by Kyoeisha Chemical Co., Ltd., non-volatile content: 100% by weight), 0.5 parts by weight of antioxidant (phenolic antioxidant Irganox 1010), 0.1 parts by weight of ultraviolet light absorber (Tinuvin 326), 0.5 weight part of processing aid (mixture of paraffin oil and erucamide) was mixed in a high-speed mixer, then kneaded at 135°C, and then extruded into strip sheets; at this time, the dielectric constant of the matrix resin was 2.23, the melting peak temperature was 147.7°C, and the gel content was 37% at a radiation dose of 25 Mrad.

[0163] The extruded resin sheet is irradiated on both sides with electron rays, the irradiation energy is 2.5 MeV, the irradiation dose is 25 Mrad, so that the resin sheet is cross-linked;

[0164] The cross-linked resin sheet was then sent to a heating furnace for foaming at 240°C, and then the temperature was lowered to 120°C for biaxial stretching, with the sheet being stretched 3.0 times in the TD direction and 2.8 times in the MD direction.

[0165] Then, a calendering step is performed, and the calendering pressure and calendering speed are controlled so that a 510 μm polymer porous sheet is obtained after calendering.

[0166] Example 6

[0167] 40 parts by weight of polyolefin plastomer (POP, trade name: AFFINITY™ PL 1850G), 60 parts by weight of cross-linkable polypropylene (PP, trade name: HC300B), 10 parts by weight of foaming masterbatch containing 95 wt% of azobisisobutyronitrile and 5 wt% of zinc oxide, 0.5 parts by weight of trimethylolpropane trimethacrylate (cross-linking aid, trade name; Light Ester TMP, manufactured by Kyoeisha Chemical Co., Ltd., non-volatile component: 100% by weight), 0.5 parts by weight of antioxidant (phenolic antioxidant Irganox 1010), 0.1 parts by weight of ultraviolet light absorber (Tinuvin 326), and 0.5 parts by weight of processing aid (a mixture of paraffin oil and erucamide) are mixed in a high-speed mixer, then kneaded at 135°C, and then extruded into strip sheets; at this time, the dielectric constant of the matrix resin is 2.31 The melting peak temperature is 145.1°C and the gel content is 61% at a radiation dose of 25 Mrad.

[0168] The extruded resin sheet was irradiated on both sides by electron beams, with an irradiation energy of 1.5 MeV and an irradiation dose of 25.2 Mrad, so that the resin sheet was cross-linked;

[0169] The cross-linked resin sheet was then sent to a heating furnace for foaming at 200°C, and then the temperature was lowered to 120°C for biaxial stretching, with the sheet being stretched 1.5 times in the TD direction and 1.8 times in the MD direction.

[0170] Then, a calendering step is performed, and the calendering pressure and calendering speed are controlled so that a 50 μm polymer porous sheet is obtained after calendering.

[0171] Example 7

[0172] 20 parts by weight of linear low-density polyethylene (LLDPE, trade name: Hanhua CLBA-8250BK), 20 parts by weight of polyolefin plastomer (POP, trade name: AFFINITY™ PL 1850G), 60 parts by weight of cross-linkable polypropylene (PP, trade name: HC300B), 10 parts by weight of foaming masterbatch containing 95 wt% of azobisisobutyronitrile and 5 wt% of zinc oxide, 0.5 parts by weight of trimethylolpropane trimethacrylate (cross-linking aid, trade name; Light Ester TMP, manufactured by Kyoeisha Chemical Co., Ltd., non-volatile component: 100% by weight), 0.5 parts by weight of antioxidant (phenolic antioxidant Irganox 1010), 0.1 parts by weight of ultraviolet light absorber (Tinuvin 326), 0.5 weight part of processing aid (mixture of paraffin oil and erucamide) was mixed in a high-speed mixer, then kneaded at 135°C, and then extruded into strip sheets; at this time, the dielectric constant of the matrix resin was 2.31, the melting peak temperature was 145.1°C, and the gel content was 61% at a radiation dose of 25 Mrad.

[0173] The extruded resin sheet was irradiated on both sides with electron beams, with an irradiation energy of 1.5 MeV and an irradiation dose of 12.5 rad, so that the resin sheet was cross-linked;

[0174] The cross-linked resin sheet was then sent to a heating furnace for foaming at 200°C, and then the temperature was lowered to 120°C for biaxial stretching, with the sheet being stretched 1.5 times in the TD direction and 1.8 times in the MD direction.

[0175] Then, a calendering step is performed, and the calendering pressure and calendering speed are controlled so that a 1950 μm polymer porous sheet is obtained after calendering.

[0176] Comparative Example 1

[0177] 5 parts by weight of linear low-density polyethylene (LLDPE, trade name: Hanwha CLBA-8250BK), 5 parts by weight of polyolefin plastomer (POP, trade name: AFFINITY™ PL 1850G), 90 parts by weight of cross-linkable polypropylene (PP, trade name: HC300B), 10 parts by weight of foaming masterbatch containing 95 wt% of azobisisobutyronitrile and 5 wt% of zinc oxide, 0.5 parts by weight of trimethylolpropane trimethacrylate (cross-linking aid, trade name; Light Ester TMP, manufactured by Kyoeisha Chemical Co., Ltd., non-volatile content: 100% by weight), 0.5 parts by weight of antioxidant (phenolic antioxidant Irganox 1010), 0.1 parts by weight of ultraviolet light absorber (Tinuvin 326), 0.5 weight part of processing aid (mixture of paraffin oil and erucamide) was mixed in a high-speed mixer, then kneaded at 135°C, and then extruded into strip sheets; at this time, the dielectric constant of the matrix resin was 2.17, the melting peak temperature was 153.5°C, and the gel content was 27% at a radiation dose of 25 Mrad.

[0178] The extruded resin sheet was irradiated on both sides with electron rays, with an irradiation energy of 1.5 MeV and an irradiation dose of 15.3 Mrad, so that the resin sheet was cross-linked;

[0179] The cross-linked resin sheet was then sent to a heating furnace for foaming at 200°C, and then the temperature was lowered to 120°C for biaxial stretching, with the sheet being stretched 1.5 times in the TD direction and 1.8 times in the MD direction.

[0180] Then, a calendering step is performed, and the calendering pressure and calendering speed are controlled so that a 230 μm polymer porous sheet is obtained after calendering.

[0181] Comparative Example 2

[0182] 40 parts by weight of linear low-density polyethylene (LLDPE, trade name: Hanhua CLBA-8250BK), 40 parts by weight of polyolefin plastomer (POP, trade name: AFFINITY™ PL 1850G), 20 parts by weight of cross-linkable polypropylene (PP, trade name: HC300B), 10 parts by weight of foaming masterbatch containing 95 wt% of azobisisobutyronitrile and 5 wt% of zinc oxide, 0.5 parts by weight of trimethylolpropane trimethacrylate (cross-linking aid, trade name; Light Ester TMP, manufactured by Kyoeisha Chemical Co., Ltd., non-volatile content: 100% by weight), 0.5 parts by weight of antioxidant (phenolic antioxidant Irganox 1010), 0.1 parts by weight of ultraviolet light absorber (Tinuvin 326), 0.5 weight part of processing aid (mixture of paraffin oil and erucamide) was mixed in a high-speed mixer, then kneaded at 135°C, and then extruded into strip sheets; at this time, the dielectric constant of the matrix resin was 2.39, the melting peak temperature was 132.3°C, and the gel content was 88% at a radiation dose of 25 Mrad.

[0183] The extruded resin sheet was irradiated on both sides with electron beams, with an irradiation energy of 1.5 MeV and an irradiation dose of 12.5 Mrad, so that the resin sheet was cross-linked;

[0184] The cross-linked resin sheet was then sent to a heating furnace for foaming at 200°C, and then the temperature was lowered to 120°C for biaxial stretching, with the sheet being stretched 1.5 times in the TD direction and 1.8 times in the MD direction.

[0185] Then, a calendering step is performed, and the calendering pressure and calendering speed are controlled so that a 2500 μm polymer porous sheet is obtained after calendering.

[0186] Comparative Example 3

[0187] 20 parts by weight of linear low-density polyethylene (LLDPE, trade name: Hanhua CLBA-8250BK), 20 parts by weight of polyolefin plastomer (POP, trade name: AFFINITY™ PL 1850G), 60 parts by weight of cross-linkable polypropylene (PP, trade name: HC300B), 20 parts by weight of foaming masterbatch containing 95 wt% of azobisisobutyronitrile and 5 wt% of zinc oxide, 0.1 parts by weight of trimethylolpropane trimethacrylate (cross-linking aid, trade name; Light Ester TMP, manufactured by Kyoeisha Chemical Co., Ltd., non-volatile content: 100% by weight), 0.5 parts by weight of antioxidant (phenolic antioxidant Irganox 1010), 0.1 parts by weight of ultraviolet light absorber (Tinuvin 326), 0.5 weight part of processing aid (mixture of paraffin oil and erucamide) was mixed in a high-speed mixer, then kneaded at 135°C, and then extruded into strip sheets; at this time, the dielectric constant of the matrix resin was 2.31, the melting peak temperature was 145.1°C, and the gel content was 61% at a radiation dose of 25 Mrad.

[0188] The extruded resin sheet is irradiated on both sides with electron rays, the irradiation energy is 0.5 Mev, the irradiation dose is 12.5 Mrad, so that the resin sheet is cross-linked;

[0189] The cross-linked resin sheet was then sent to a heating furnace for foaming at 300°C, and then the temperature was lowered to 120°C for biaxial stretching, with the sheet being stretched 1.1 times in the TD direction and 1.1 times in the MD direction.

[0190] Then, a calendering step is performed, and the calendering pressure and calendering speed are controlled so that a 300 μm polymer porous sheet is obtained after calendering.

[0191] Comparative Example 4

[0192] 20 parts by weight of linear low-density polyethylene (LLDPE, trade name: Hanhua CLBA-8250BK), 20 parts by weight of polyolefin plastomer (POP, trade name: AFFINITY™ PL 1850G), 60 parts by weight of cross-linkable polypropylene (PP, trade name: HC300B), 3 parts by weight of foaming masterbatch containing 95 wt% of azobisisobutyronitrile and 5 wt% of zinc oxide, 0.5 parts by weight of trimethylolpropane trimethacrylate (cross-linking aid, trade name; Light Ester TMP, manufactured by Kyoeisha Chemical Co., Ltd., non-volatile component: 100% by weight), 0.5 parts by weight of antioxidant (phenolic antioxidant Irganox 1010), 0.1 parts by weight of ultraviolet light absorber (Tinuvin 326), 0.5 weight part of processing aid (mixture of paraffin oil and erucamide) was mixed in a high-speed mixer, then kneaded at 135°C, and then extruded into strip sheets; at this time, the dielectric constant of the matrix resin was 2.31, the melting peak temperature was 145.1°C, and the gel content was 61% at a radiation dose of 25 Mrad.

[0193] The extruded resin sheet was irradiated on both sides with electron beams, with an irradiation energy of 2.5 MeV and an irradiation dose of 25.5 Mrad, so that the resin sheet was cross-linked;

[0194] The cross-linked resin sheet was then sent to a heating furnace to be foamed at 160°C, and then the temperature was lowered to 120°C for biaxial stretching, with the sheet being stretched 3.5 times in the TD direction and 3.5 times in the MD direction.

[0195] Then, a calendering step is performed, and the calendering pressure and calendering speed are controlled so that a 300 μm polymer porous sheet is obtained after calendering.

[0196] Comparative Example 5

[0197] 15 parts by weight of linear low-density polyethylene (LLDPE, trade name: Hanhua CLBA-8250BK), 85 parts by weight of cross-linkable polypropylene (PP, trade name: HC300B), 10 parts by weight of foaming masterbatch containing 95 wt% of azobisisobutyronitrile and 5 wt% of zinc oxide, 0.5 parts by weight of trimethylolpropane trimethacrylate (cross-linking aid, trade name; Light Ester TMP, manufactured by Kyoeisha Chemical Co., Ltd., non-volatile component: 100% by mass), 0.5 parts by weight of antioxidant (phenolic antioxidant Irganox 1010), 0.1 parts by weight of ultraviolet light absorber (Tinuvin 326), and 0.5 parts by weight of processing aid (a mixture of paraffin oil and erucamide) were mixed in a high-speed mixer, then kneaded at 135° C., and then extruded into strip sheets; at this time, the dielectric constant of the matrix resin was 2.28 The peak melting temperature is 152.4°C and the gel content is 32% at a radiation dose of 25 Mrad.

[0198] The extruded resin sheet was irradiated on both sides with electron rays, with an irradiation energy of 1.5 MeV and an irradiation dose of 15.3 Mrad, so that the resin sheet was cross-linked;

[0199] The cross-linked resin sheet was then sent to a heating furnace for foaming at 200°C, and then the temperature was lowered to 120°C for biaxial stretching, with the sheet being stretched 1.5 times in the TD direction and 1.8 times in the MD direction.

[0200] Then, a calendering step is performed, and the calendering pressure and calendering speed are controlled so that a 200 μm polymer porous sheet is obtained after calendering.

[0201] Comparative Example 6

[0202] 20 parts by weight of linear low-density polyethylene (LLDPE, trade name: Hanhua CLBA-8250BK), 20 parts by weight of polyolefin plastomer (POP, trade name: AFFINITY™ PL 1850G), 60 parts by weight of cross-linkable low-density polyethylene, 10 parts by weight of foaming masterbatch containing 95 wt% of azobisisobutyronitrile and 5 wt% of zinc oxide, 0.5 parts by weight of trimethylolpropane trimethacrylate (cross-linking aid, trade name; Light Ester TMP, manufactured by Kyoeisha Chemical Co., Ltd., non-volatile component: 100% by weight), 0.5 parts by weight of antioxidant (phenolic antioxidant Irganox 1010), 0.1 parts by weight of ultraviolet light absorber (Tinuvin 326), 0.5 weight part of processing aid (mixture of paraffin oil and erucamide) was mixed in a high-speed mixer, then kneaded at 135°C, and then extruded into strip sheets; at this time, the dielectric constant of the matrix resin was 2.43, the melting peak temperature was 123.1°C, and the gel content was 76% at a radiation dose of 25 Mrad.

[0203] The extruded resin sheet was irradiated on both sides with electron rays, with an irradiation energy of 1.5 MeV and an irradiation dose of 15.3 Mrad, so that the resin sheet was cross-linked;

[0204] The cross-linked resin sheet was then sent to a heating furnace for foaming at 200°C, and then the temperature was lowered to 120°C for biaxial stretching, with the sheet being stretched 1.5 times in the TD direction and 1.8 times in the MD direction.

[0205] Then, a calendering step is performed, and the calendering pressure and calendering speed are controlled so that a 230 μm polymer porous sheet is obtained after calendering.

[0206] Then, Examples 1-7 and Comparative Examples 1-6 were placed in an electric field of -8 kV / mm at room temperature for 20 seconds, and the distance d between the corona needle and the surface of the polymer porous sheet was set to 4 cm. Polarized polymer porous sheets of Examples 1-7 and Comparative Examples 1-6 were obtained, and the dielectric strength and piezoelectric constant were measured.

[0207] The structural characteristics of Examples 1-7 and Comparative Examples 1-6 are shown in Table 1 below:

[0208] Table 1

[0209]

[0210] The physical and chemical properties of Examples 1-7 and Comparative Examples 1-6 are shown in Table 2 below:

[0211] Table 2

[0212]

[0213] It can be seen that Comparative Example 1 due to D zd The small average pore size leads to D zd The proportion of 5μm-50μm is low, and its 10% compressive stress is too large, which shows poor flexibility. At the same time, the pores of the polymer porous sheet are small, the continuity of the polymer matrix is ​​increased, and the deformation of the polymer chain and the reorientation of the polar groups are crucial for the generation of charge. It can be seen from the piezoelectric constant that is smaller than that of the embodiment that if the pores are too dense, the movement of the polymer chain may be restricted, thereby reducing the amount of charge generated under mechanical stress, resulting in a decrease in the piezoelectric constant of the material; Comparative Example 3 due to D zd The large average pore size leads to D zd The proportion of 5μm-50μm is low, and the proportion of the polymer matrix in the thickness direction is too low, which reflects its insufficient dielectric strength, excessive dimensional change rate at 60°C, and too small 10% compressive stress; Comparative Example 2 does not fall within the range in thickness and density, and its piezoelectric constant, elongation at break and dimensional change rate at 60°C are not ideal; In Comparative Example 4, the proportion of the polymer matrix in the thickness direction is too high, polarization is difficult, and corona breakdown occurs when the polarization voltage is increased; Comparative Example 5 introduces a polypropylene resin with a higher melting peak and is not easy to cross-link, resulting in a bimodal distribution of large and small pores in the thickness direction, resulting in D zd The proportion of 5μm-50μm is low, and the piezoelectric constant and 10% compressive stress are not ideal; after LDPE is used to replace PP in comparative example 6, the proportion of the melting peak is 0, and thus the piezoelectric constant and the dimensional change rate at 60°C do not meet the requirements at all.

[0214] The present invention can be implemented in other forms than those described above without departing from the spirit and scope of the present invention. The embodiments disclosed in the present application are examples and are not limited to these.

Claims

1. A multilayer piezoelectric electret film element, comprising in sequence a first conductive layer (2), a flexible porous film layer (3) and a second conductive layer (4), characterized in that: The flexible porous film layer (3) comprises a polymer porous sheet, the thickness H of the polymer porous sheet is 50 μm-2000 μm, and the density is 100-900 kg / m 3 ; D zd The pores in the range of 5 μm to 50 μm account for more than 80% of the total pores in the polymer porous sheet. zd It is defined as the maximum bubble diameter of a single bubble in the thickness direction; H p / H is 5%-60%, H p It is defined as the average value of the cumulative thickness of the polymer matrix after excluding the pores in the thickness direction, and H is defined as the thickness of the polymer porous sheet; And the dielectric strength of the polymer porous sheet in the thickness direction is 10-60 MV / m.

2. The piezoelectric electret thin film element according to claim 1, characterized in that: A base support layer (1) is also compounded on the other side of the first conductive layer (2), and an outer covering layer (5) is also compounded on the other side of the second conductive layer (4).

3. The piezoelectric electret thin film element according to claim 1, characterized in that: There is gas in the pores of the polymer porous sheet, and the gas includes: air, nitrogen, oxygen, argon, carbon dioxide, fluorine, chlorine, and water vapor; and the piezoelectric electret sheet is formed by subjecting the polymer porous sheet to electrodeposition and surface metallization treatment.

4. A polymer porous sheet, characterized in that: The thickness H of the polymer porous sheet is 50 μm-2000 μm, and the density is 100-900 kg / m 3 ; D zd The pores in the range of 5 μm to 50 μm account for more than 80% of the total pores in the polymer porous sheet. zd It is defined as the maximum bubble diameter of a single bubble in the thickness direction; H p / H is 5%-60%, H p It is defined as the average value of the cumulative thickness of the polymer matrix after excluding the pores in the thickness direction, and H is defined as the thickness of the polymer porous sheet; And the dielectric strength of the polymer porous sheet in the thickness direction is 10-60 MV / m.

5. The polymer porous sheet according to claim 4, characterized in that: The polymer porous sheet contains at least a polypropylene resin.

6. The polymer porous sheet according to claim 4, characterized in that: The matrix resin of the polymer porous sheet refers to a blended resin obtained by melt blending at least two or more blended polyolefin resins but not yet crosslinked and foamed. The matrix resin has a dielectric constant of 2.2-2.4 and a melting peak temperature of 135-150°C.

7. The polymer porous sheet according to claim 6, characterized in that: The standard cross-linking degree of the matrix resin of the polymer porous sheet is 40-80% when the radiation dose is 25 Mrad.

8. The polymer porous sheet according to claim 4, characterized in that: The polymer porous sheet is a cross-linked foamed sheet with a cross-linking degree of 10-70%.

9. The polymer porous sheet according to claim 4, characterized in that: The polymer porous sheet comprises a xylene soluble part and a xylene insoluble part; wherein the area of ​​the soluble part with a DSC melting temperature above 130° C. accounts for 10%-40% of the total area of ​​the DSC melting temperature.

10. The polymer porous sheet according to claim 4, characterized in that: The polymer porous sheet has a dimensional change rate at 60° C. of −5% to 5%.

11. The polymer porous sheet according to claim 4, characterized in that: The elongation at break of the polymer porous sheet is greater than 100%, and the 10% compressive stress is 5KPa-150KPa.

12. A method for preparing a porous polymer sheet according to claim 4, characterized in that: The polymer porous sheet is made by foaming a base resin, wherein the base resin refers to a blended resin comprising at least two or more blended polyolefin resins that are melt-blended but not cross-linked and foamed, the base resin has a dielectric constant of 2.2-2.4, a melting peak temperature of 135-150° C., and a standard cross-linking degree of 40-80% at a radiation dose of 25 Mrad; The matrix resin is sequentially subjected to extrusion molding, electron beam radiation cross-linking, normal pressure high temperature foaming, biaxial stretching, and calendering to obtain a polymer porous sheet for a piezoelectric electret.